Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/jcp.25982
|View full text |Cite
|
Sign up to set email alerts
|

ABC of multifaceted dystrophin glycoprotein complex (DGC)

Abstract: Dystrophin protein in association with several other cellular proteins and glycoproteins leads to the formation of a large multifaceted protein complex at the cell membrane referred to as dystrophin glycoprotein complex (DGC), that serves distinct functions in cell signaling and maintaining the membrane stability as well as integrity. In accordance with this, several findings suggest exquisite role of DGC in signaling pathways associated with cell development and/or maintenance of homeostasis. In the present r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 205 publications
1
19
0
Order By: Relevance
“…The reason for increase in stem diameter with the increase in vermicompost level might be due to availability of vital nutrients for plant growth by vermicompost which resulted more photosynthate formation and let the plant to increase its vegetative growth. Similar findings are in line with [21] and [22] who found that application of vermicompost increased stem diameter in tomato plants. Variation among the cultivars in stem diameter might be due to their genetic makeup.…”
Section: Stem Diameter (Cm)supporting
confidence: 91%
“…The reason for increase in stem diameter with the increase in vermicompost level might be due to availability of vital nutrients for plant growth by vermicompost which resulted more photosynthate formation and let the plant to increase its vegetative growth. Similar findings are in line with [21] and [22] who found that application of vermicompost increased stem diameter in tomato plants. Variation among the cultivars in stem diameter might be due to their genetic makeup.…”
Section: Stem Diameter (Cm)supporting
confidence: 91%
“…In Duchenne muscular dystrophy, alterations in the expression of members of the dystrophin network are closely related to key pathophysiological features in dystrophin-deficient muscles, including degeneration-regeneration cycles, progressive fiber degeneration, fibrosis and chronic inflammation. Detailed reviews have been published on the composition of the core dystrophin complex [19,[56][57][58], as well as the role of dystrophin and its associated glycoprotein complex in the multisystemic complications of dystrophinopathy and pathophysiological crosstalk throughout the body [34][35][36][37]59]. Therefore, this article does not attempt to recapitulate these biochemical and pathobiochemical issues in detail, but refers instead to specific aspects that are crucial for our general understanding of the wider functional role of the dystrophin complexome in normal skeletal muscle tissue.…”
Section: Vimentin Synemin Plectinmentioning
confidence: 99%
“…Two POPDC-interacting proteins, who are expressed in both cardiac and skeletal muscle are dystrophin and dysferlin [19]. Dystrophin is an actin-binding protein with a subsarcolemmal localization and part of the dystrophin-associated glycoprotein complex (DGC) and links laminin in the basal lamina to the actin cytoskeleton [37]. Moreover, dystrophin also serves as a scaffold for a number of signalling proteins [38].…”
Section: Protein-protein Interaction Of the Popeye Domain In Striated Muscle Cellsmentioning
confidence: 99%